Phylogeography of three endemic birds of Maratua Island, a potential archive of Bornean biogeography - Chua, Vivien L.; Mustafa, Abdul Rahman; Phillipps, Quentin; Lim, Haw Chuan; Taylor, Sabrina S. (National University of Singapore, 2015)
Maratua is an oceanic island ca. 50 km off the east coast of Borneo and home to several endemic taxa of birds and mammals. To determine the phylogeographic relationships of three of Maratua’s most distinctive avian endemics—a shama Copsychus stricklandii barbouri, a bulbul Pycnonotus atriceps hodiernus, and a monarch Hypothymis azurea aeria—we compared their mitochondrial ND2 sequences with those of putatively closely related Southeast Asian populations. We found that Maratua’s shama and bulbul are substantially differentiated from populations on Borneo and elsewhere in Southeast Asia, whereas Maratua’s monarch is not. The shama’s phylogeographic tree indicates a sister relationship between C. s. barbouri and C. s. stricklandii of northeast Borneo, both of which have white crowns (ND2 distance ~2%). These two taxa, in turn, are >3% divergent from C. malabaricus populations, which have black crowns. The relative morphological and genetic similarity of C. s. barbouri and C. s. stricklandii suggests that C. stricklandii had a broader distribution in eastern Borneo in the mid-Pleistocene and that C. s. stricklandii has more recently moved or been restricted to its current position in northeast Borneo. Maratua has thus acted as a biogeographic “museum”, preserving evidence of C. stricklandii’s former distribution. The Maratuan P. atriceps is about equidistant genetically from other P. atriceps populations. It is distinguished by an overall grey body plumage, whereas P. atriceps elsewhere is mostly yellow (with grey morphs appearing only rarely). The universality of grey birds on Maratua is likely the result of a founder effect. The Maratuan monarch’s genetic similarity to the mainland Bornean population suggests either that it is a recent invader or that substantial gene flow occurs between Borneo and Maratua in this species. The genetic and morphological distinctiveness of the shama and bulbul are adequate to consider them both as full species.